Pengaruh Kombinasi Media Tanam dan Debit Pacar Irigasi Tetes Terhadap Pertumbuhan dan Produksi Sawi - Megi Saputra; Ridwan Ridwan; Elhamida Rezkia Amien; Muhammad Amin (Jurnal Agricultural Biosystem Engineering, 2022)
To meet the increasing needs of consumers, both in terms of quality and quantity, it is necessary to increase the production of mustard plants through fertilization and irrigation. One of the efforts that can be done to overcome the limited availability of water in the land is to use water-saving irrigation technology. Utilization of sandy land such as coastal areas is one solution to overcome the limitations of agricultural land. However, coastal sandy land cannot be used optimally by the community around the coast for agricultural activities, because so far the beach sand land is considered unfit as a planting medium. That to maximize the use of sand as a vegetable growing medium, additional fertilizer is needed. The method used in this study was a completely randomized design (RAL) with two factors, namely the first factor (M) a combination of planting media with 3 combinations, namely K1, M1, M2 and M3. While the second factor (D) drip irrigation discharge with 3 discharges, namely D1 (100 ml/day), D2 (150 ml/day) and D3 (200 ml/day). Each treatment was repeated 3 times. The combination of planting media affects the growth and production of mustard (Brassica juncea L.) plants with the best combination of planting media, namely M2 (sand above and compost below). Discharge drip irrigation affects the growth and production of mustard (Brassica juncea L.) with the best yield of D1 (100 ml/day). The interaction between the combination of planting media and drip irrigation discharge on the growth and production of the best mustard (Brassica juncea L.) plant is M2D1.